Reliability of parent report measures of behaviour in children with Down syndrome. Issue 9 (18th July 2018) - Esbensen, A. J.; Hoffman, E. K.; Shaffer, R.; Chen, E.; Patel, L.; Jacola, L.
Abstract: Background: Behavioural problems are common among children with Down syndrome (DS). Tools to detect and evaluate maladaptive behaviours have been developed for typically developing children and have been evaluated for use among children with intellectual and developmental disabilities. However, these measures have not been evaluated for use specifically in children with DS. This psychometric evaluation is important given that some clinically observed behaviours are not addressed in currently available rating scales. The current study evaluates the psychometric properties of the Child Behavior Checklist (CBCL), a commonly used screening tool developed for typically developing children and commonly used with children with intellectual and developmental disabilities. Methods: The study investigated the psychometric properties of the CBCL among school‐aged children with DS, including an assessment of the rate of detecting behaviour problems, concerns with distribution, internal consistency, inter‐rater reliability and convergent and discriminant validity with the Aberrant Behavior Checklist and Nisonger Child Behavior Rating Form. Caregivers of 88 children with DS aged 6–18 years rated their child's behaviour with the CBCL, Aberrant Behavior Checklist and Nisonger Child Behavior Rating Form. Teachers completed the Teacher Report Form. Results: About one‐third of children with DS were reported to exhibit behaviours of clinical concern on the total score of the CBCL. Internal consistency for CBCL sub‐scales was poor to excellent, and inter‐rater reliability was generally acceptable. The sub‐scales of the CBCL performed best when evaluating convergent validity, with variable discriminant validity. Normative data conversions controlled for age and gender differences in this sample. Conclusions: The study findings suggest that, among children with DS, some CBCL sub‐scales generally performed in a psychometrically sound and theoretically appropriate manner in relation to other measures of behaviour. Caution is warranted when interpreting specific sub‐scales (Anxious/Depressed, Somatic Complaints and Thought Problems). The CBCL can continue to be used as a screening measure when evaluating behavioural concerns among children with DS, acknowledging poor discriminant validity and the possibility that key behaviour concerns in DS may not be captured by the CBCL screen.